Reconceptualizing learning designs in higher education: Using mobile devices to engage students in authentic tasks - Ostashewski, N.; Dickinson, Sonia; Martin, R. (IGI Global, 2015)
© 2015, IGI Global. All rights reserved. This goal of this chapter is to provide a design and development roadmap for the adaptation of traditional classroom activities into engaging iPad-based digital learning activities. Reporting on an ongoing longitudinal case study, the chapter provides an overview of rationale and design considerations of the authentic iPad learning design implementation project, and the outcomes and improvements made over time. The iPad activities described provide further details of the approach taken and adaptations made. Since implementing iPad activities into this higher education environment several terms ago, the lecturer reports significantly higher levels of student engagement. Additionally, students report that the classroom activities in the post-graduate marketing course are authentic, transferrable, and are more engaging due the use of the iPad-based activities.